The effectiveness of template and example paper implementation in developing student writing skills in science courses - Muhammad Syazali; Muhammad Erfan; Baiq Niswatul Khair; Aisa Nikmah Rahmatih; Hasnawati Hasnawati (Jurnal Pijar Mipa, 2023)
The use of templates and examples of papers separately is proven to be able to develop students' writing skills. The average degree of mastery that can be achieved is already in the good category. Using various learning facilities can be a solution to improve these achievements into a very good category. This study aims to analyze the effectiveness of implementing templates and sample papers in developing students' writing skills in science courses. The pre-experimental research was conducted on elementary school teacher education study program students. Data on each student's scientific research paper writing skills were collected using the documentation method. This data was then analyzed descriptively. The descriptive analysis includes average and proportion measurements. Based on the results of data analysis, it was found that the average student's skills in writing papers were in a good category. Most students have very good (41.44%) and good (40.54%) categories of writing skills. 13 indicators have reached the very good category, one indicator is in a good category, and two indicators are in the sufficient category. The rests are one indicator still in the less category and four indicators in the less category. The conclusion that can be drawn from this research results is using examples and paper templates as effective learning facilities to improve students' writing skills.